[Group Exploring Snæfellsnes Peninsula] - Streng, Evelyn Fiedler (1975)
Photograph of a group of people exploring Snæfellsnes Peninsula. They stand on orange rocks beside a blue river and a wall of grey rocks. A dark plain is visible in the distance to the right. Power lines cross the top of the photograph, attached to a metal pole.